Establishing a management system for Pink Gems School: an action research approach - Munyi, Magdalene Wambere (Strathmore University, 2020)
Pink Gems Kindergarten was started in the year 2011 and construction of the school completed a year after. The land on which the school was built was on a leasehold agreement for a period of 5 years from 2012 to 2017. For a period of 5 years since its commencement, the school did not have a management structure and operated with the proprietors as the acting directors and a few teachers. the resulting issues that followed included misappropriation of school funds as well as theft, lack of records both academic and administrative, little to no follow up on the legal processes and non-compliance to the ministerial requirements. All these issues led to a grave disagreement between the proprietors and the land owner which led to an auction and eventual demolition of one part of the school. The study focused on establishing a management system for Pink Gems School, and this was done between September 2019 and April 2020. It involved the three directors and three teachers. I used the Action Research four-phase approach. Phase I was planning and it included a brief overview of different management structures with specific context to global, regional and local settings with a view to highlighting the goals and management structures applicable for pink gems school. Phase II was acting, where, together with my critical peer, we operationalized the goals and management structures for Pink Gems. Phase III was Observation, where we had detailed monitoring, and recording of progress and any change requiring intervention. Phase IV was Reflection, to concretize the goals and management structures that had been setup. The goals and management structures established for Pink Gems included classroom experience, motivation and seamless administration, as well as focus on rules, focus on hierarchy, clarity of roles and certification and innate capacities respectively. These goals were very specific to Pink Gems and were the foundational point of establishing a management system, and it will be useful to other school owners particularly those whose schools need to establish a management system and those that are family run.
Submitted in partial fulfillment of the requirements for the degree of Master’s in Education Management at Strathmore University.
Keywords: School Management System; Pink Gems School; Action Research Approach